Shelf life and sensory assessment of tilapia quenelle during frozen storage - Angelini, Maria Fernanda Calil (2013)
The objective of this work was to evaluate the shelf life and sensory attributes of tilapia quenelle. Treatments consisted of two types of packages – polyethylene zipper (retort pouch) (QA) and polyethylene waxed paper box (QB) – stored at -18°C for 120 days. Tilapia quenelle was stable for all parameters established by Brazilian legislation. Average values of the evaluated attributes in different packages, during storage, showed no significant difference, except for the “refrigeration” flavor. However, during the storage period, there were significant differences for sensory attributes, as “moist appearance”, fish and product aroma, and off flavors of “mud” and “refrigeration”. Preserving product quality as for its sensory attributes, during storage, shows that tilapia quenelle is a convenience product and contributes to the increase of fish consumption.